Head and Neck Mesenchymal Neoplasms With GLI1 Gene Alterations: A Pathologic Entity With Distinct Histologic Features and Potential for Distant Metastasis. (June 2020) - Xu, Bin; Chang, Koping; Folpe, Andrew L.; Kao, Yu-Chien; Wey, Shiuan-Li; Huang, Hsuan-Ying; Gill, Anthony J.; Rooper, Lisa; Bishop, Justin A.; Dickson, Brendan C.; Lee, Jen-Chieh; Antonescu, Cristina R.
Abstract : Soft tissue tumors with GLI1 gene fusions or amplifications have been recently described as a unique pathologic entity with an established risk of malignancy. We herein expand these findings by investigating a cohort of 11 head and neck lesions with GLI1 alterations, including 8 from the tongue, for their clinicopathologic and molecular features. The tumors commonly affected males in their 30s (male:female ratio 2.7:1; range: 1 to 65). Tumors showed a multinodular growth pattern, nested architecture separated by a delicate, arborizing vascular network, monotonous round to ovoid nuclei, and clear cytoplasm. Tumor protrusion into vascular spaces was common. Genetic alterations were investigated by fluorescence in situ hybridization and/or targeted RNA sequencing. Seven tumors harbored GLI1 fusions with the following partners: ACTB (n=4), PTCH1 (n=2), or MALAT1 (n=1). The remaining 4 cases showed coamplifications of GLI1 with CDK4 and MDM2 genes. Tumors were commonly positive for S100 protein and CD56. CDK4, MDM2, and STAT6 were positive in GLI1 -amplified tumors. Two of 6 patients with available follow-up (1 each with GLI1 amplification and PTCH1-GLI1 fusion) developed distant metastases. Both tumors showed a high mitotic index and tumor necrosis. The head and neck region, particularly tongue, is a common location for GLI1 -related mesenchymal tumors. Although a morphologic overlap was noted with the previously reported "pericytoma with t(7, 12) translocation, " often occurring in the tongue, our findings expand the original findings, to include a more variable immunophenotype, propensity for late distant metastases, and alternative mechanisms of GLI1 oncogenic activation, such as various GLI1 fusion partners or GLI1 coamplifications with MDM2 and CDK4 genes. Abstract : Supplemental Digital Content is available in the text.